2022
DOI: 10.1021/acsanm.2c00240
|View full text |Cite
|
Sign up to set email alerts
|

Ru Nanoclusters Supported on Ti3C2Tx Nanosheets for Catalytic Hydrogenation of Quinolines

Abstract: Ru-based catalysts hold great promise for selective hydrogenation of quinolines. However, the slow desorption of active H and strong adsorption of hydrogenated substrates on the Ru active sites seriously hinder their industrial applications. Herein, we design Ti3C2T x -supported Ru nanocluster catalysts by loading Ru nanoclusters on two-dimensional (2D) Ti3C2T x nanosheets. The Ti3C2T x nanosheets with unique 2D structure and rich surface-terminated functional groups afford the formed Ru nanoclusters (RuNCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Under the same conditions, the selective partial reduction of 3‐acetylquinoline and 3‐quinolinecarboxaldehyde was accompanied by reduction of the carbonyl group to afford 1‐(1,2‐dihydroquinolin‐3‐yl)ethan‐1‐ol and (1,2‐dihydroquinolin‐3‐yl)methanol, respectively, as the sole product at complete conversion with no evidence for either tetrahydroquinoline (Table 2, entries 13–14). When the transfer hydrogenation of 3‐acetylquinoline and 3‐quinolinecarboxaldehyde was conducted at room temperature under otherwise identical conditions, the acyl and aldehyde groups were rapidly and quantitatively reduced to afford 1‐(quinolin‐3‐yl)ethan‐1‐ol and quinolin‐3‐ylmethanol, respectively, after only 60 min; selective partial reduction to the corresponding dihydroquinoline was then achieved by adding a further five equivalents of dimethylamine borane and increasing the reaction temperature to 65 °C for 6 h. While it is tempting to attribute this selective partial reduction to the steric influence of the substituent, there are very few reports of the selective reduction of this class of substrate and AuNPs supported on amine functionalised silica, [34,38] nanolayered Co−Mo sulfides, [55] ruthenium nanoclusters supported on Ti 3 C 2 T x nanosheets, [50] PEG‐stabilised rhodium nanoparticles, [12] NiNPs in porous carbon [31d] and RuNPs stabilised in silica nanospheres coated with a microporous silica layer, RuSiO 2 @mSiO 2 , [33c] all catalyse the reduction of 3‐substituted quinolines to afford high yields of the corresponding tetrahydroquinoline with no evidence for the dihydroquinoline, which suggests that the substituent is not the only factor responsible for the high selectivity achieved with 2 . Moreover, reductions conducted in the presence of ten equivalents of dimethylamine borane for extended reaction times also gave the dihydroquinoline as the major species with only a minor amount of the tetrahydroquinoline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the same conditions, the selective partial reduction of 3‐acetylquinoline and 3‐quinolinecarboxaldehyde was accompanied by reduction of the carbonyl group to afford 1‐(1,2‐dihydroquinolin‐3‐yl)ethan‐1‐ol and (1,2‐dihydroquinolin‐3‐yl)methanol, respectively, as the sole product at complete conversion with no evidence for either tetrahydroquinoline (Table 2, entries 13–14). When the transfer hydrogenation of 3‐acetylquinoline and 3‐quinolinecarboxaldehyde was conducted at room temperature under otherwise identical conditions, the acyl and aldehyde groups were rapidly and quantitatively reduced to afford 1‐(quinolin‐3‐yl)ethan‐1‐ol and quinolin‐3‐ylmethanol, respectively, after only 60 min; selective partial reduction to the corresponding dihydroquinoline was then achieved by adding a further five equivalents of dimethylamine borane and increasing the reaction temperature to 65 °C for 6 h. While it is tempting to attribute this selective partial reduction to the steric influence of the substituent, there are very few reports of the selective reduction of this class of substrate and AuNPs supported on amine functionalised silica, [34,38] nanolayered Co−Mo sulfides, [55] ruthenium nanoclusters supported on Ti 3 C 2 T x nanosheets, [50] PEG‐stabilised rhodium nanoparticles, [12] NiNPs in porous carbon [31d] and RuNPs stabilised in silica nanospheres coated with a microporous silica layer, RuSiO 2 @mSiO 2 , [33c] all catalyse the reduction of 3‐substituted quinolines to afford high yields of the corresponding tetrahydroquinoline with no evidence for the dihydroquinoline, which suggests that the substituent is not the only factor responsible for the high selectivity achieved with 2 . Moreover, reductions conducted in the presence of ten equivalents of dimethylamine borane for extended reaction times also gave the dihydroquinoline as the major species with only a minor amount of the tetrahydroquinoline.…”
Section: Resultsmentioning
confidence: 99%
“…Gratifyingly, the TOF obtained with 2 is also comparable to or higher than the majority of these systems including RuNPs dispersed in 3D‐interconnected hierarchical porous N‐doped carbon (TOF of 654 h −1 in EtOH at 100 °C), [40] a well‐dispersed core shell nanocatalyst, Ru‐SiO 2 @mSiO 2 (TOF of 30 h −1 in water at 90 °C), [33c] thermoregulated phase‐transfer Pt nanoparticles (TOF of 193 h −1 in water at 80 °C), [15] RuNPs stabilised by a diol functionalised ionic liquid (TOF of 10 h −1 in [BMMIM]NTf 2 at 80 °C), [5] polymer supported PdNPs (TOF of 22 h −1 in MeOH/water at 80 °C), [6a,b] phosphine‐functionalised ionic liquid‐stabilised rhodium and ruthenium NPs (TOF of 20 h −1 in [BMIM][PF 6 ] at 50 °C and 71 h −1 in water at 50 °C, respectively) ][33b,41] and RuNPs supported on biomass‐derived N‐doped porous 2D‐carbon nanosheets (TOF of 96 h −1 in ethanol at 40 °C) [42] . Other relevant comparisons include PdNPs supported on amine‐rich hollow silica nanospheres (TOF of 135 h −1 in cyclohexane at 50 °C), [23a] ionic liquid stabilised NiNPs (TOF of 29 h −1 in EtOH at 75 °C), [43] NHC‐stabilised RhNPs (TOF of 496 h −1 in THF at 60 °C), [34b] PEG‐stabilized RhNPs (TOF of 182 h −1 in toluene at 80 °C), [12] 12CaO ⋅ 7Al 2 O 3 loaded with RuNPs (TOF 52 h −1 at 80 °C), [14] AuNPs and AuPt bimetallic nanoalloy nanoparticles confined in SBA‐15 (TOF of 20 h −1 in water at 100 °C and 34 h −1 in water at 25 °C), [10,17] PtRuNi/C (TOF of 329 h −1 in toluene at 100 °C), [44] Ru clusters confined in hydrogen‐bonded organic frameworks (TOF of 3 h −1 in water at 80 °C), [45] PdNPs stabilised by carbon‐metal covalent bonds (TOF of 6 h −1 in water at room temperature), [46] AuNPs supported on TiO 2 (TOF of 29 h −1 in toluene at 60 °C), [11] bimetallic CoRhNPs immobilised on an imidazolium‐based ionic liquid phase (TOF of 4 h −1 at 150 °C), [47] a RhNPs‐Lewis acid ionic liquid catalyst (TOF of 6 h −1 in [BIMIM][BF 4 ] at 80 °C), [48] PdRu@PVP (TOF of 2 h −1 , solventless at 25 °C), [49] Ru nanoclusters supported on Ti 3 C 2 T x nanosheets (TOF of 21 h −1 in ethanol/water at 55 °C), [50] RuNPs supported on nitrogen doped carbon (TOF of 20 h −1 in ethanol at 30 °C), [51] and isolated single ruthenium atoms anchored on the amine modified MOF UiO‐66‐NH 2 (TOF of 25 h −1 in THF at 100 °C) [52] . While a significantly higher TOF of 3,400 h −1 has been obtained for the hydrogenation of quinoline using RuNPs immobilised on magnesium oxide as the catalyst, reactions were conducted at 150 °C under 50 atm of hydrogen [34a] …”
Section: Resultsmentioning
confidence: 99%
“…Gaseous toluene (C 6 H 5 CH 3 ) is a dangerous VOC that is created during the process of tanning leather and other materials. Even at rather low concentrations, it is deadly to humans and very harmful to the environment [ 170 , 171 ]. To decrease the risk to one’s health from exposure to toluene gas, it is crucial to detect it early and monitor its concentration both indoors and outdoors.…”
Section: Mxene-based Gas Sensorsmentioning
confidence: 99%
“…7−9 Generally, on the surface of a metal oxide, the diffusion of Hatoms has to overcome a high energy barrier (55−236 kJ mol −1 ), 10,11 while on the surface of a noble metal, the energy barrier for dissociation of H 2 or the diffusion of H-atom is almost negligible. 12 Fortunately, water can assist H-atom diffusion across the oxide surface, also known as water-assisted proton hopping (WAPH), via the classic proton coupling electron mechanism. 13,14 Specifically, water picks up H-atoms to form a short-lived transition state of hydronium ions (H 3 O + ), accompanied by electron transfer from the H-atom to the d orbital of the metal oxides, which can promote the hydrogenation over metal oxide-supported catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic hydrogenation on metal oxide-supported nanoparticles is the highly followed standard industrial protocol for the production of both fine and bulk chemicals. In general, the diffusion of hydrogen atoms across the surface of the metal oxide-supported catalyst is crucial to the hydrogenation because the diffusion can increase the concentration of active H-atoms on the metal oxide surface during the hydrogenation. Therefore, it significantly affects the catalytic performance of metal oxide-supported catalysts. Generally, on the surface of a metal oxide, the diffusion of H-atoms has to overcome a high energy barrier (55–236 kJ mol –1 ), , while on the surface of a noble metal, the energy barrier for dissociation of H 2 or the diffusion of H-atom is almost negligible . Fortunately, water can assist H-atom diffusion across the oxide surface, also known as water-assisted proton hopping (WAPH), via the classic proton coupling electron mechanism. , Specifically, water picks up H-atoms to form a short-lived transition state of hydronium ions (H 3 O + ), accompanied by electron transfer from the H-atom to the d orbital of the metal oxides, which can promote the hydrogenation over metal oxide-supported catalysts. For example, Zhao et al reported that furfural hydrogenation on the Pd/Al 2 O 3 catalyst was accelerated by replacing the cyclohexane solvent with water.…”
Section: Introductionmentioning
confidence: 99%